2021
DOI: 10.1039/d1qi00559f
|View full text |Cite
|
Sign up to set email alerts
|

Towards 213Bi alpha-therapeutics and beyond: unravelling the foundations of efficient BiIII complexation by DOTP

Abstract: Bismuth isotopes are attracting an increasing attention for their potential applications in diagnostics and therapy. The emerging use of 213Bi in targeted α-therapy (TAT) is a particularly relevant example because...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Although the lability of Ac 3+ −py-macrodipa precludes its use with 225 Ac 3+ in nuclear medicine, the efficient formation and high stability of Bi 3+ −py-macrodipa, which surpasses Bi 3+ −macropa, suggests that this ligand is a valuable candidate for 213 Bi 3+ chelation. These results highlight that py-macrodipa joins other promising candidates for 213 Bi 3+ chelation that have arisen in recent years. , Ongoing work is directed toward the synthesis of a bifunctional analogue of py-macrodipa to apply this chelator in TAT, as well as the development of “macrodipa-type” chelators with enhanced Ac 3+ complex stabilities.…”
mentioning
confidence: 96%
“…Although the lability of Ac 3+ −py-macrodipa precludes its use with 225 Ac 3+ in nuclear medicine, the efficient formation and high stability of Bi 3+ −py-macrodipa, which surpasses Bi 3+ −macropa, suggests that this ligand is a valuable candidate for 213 Bi 3+ chelation. These results highlight that py-macrodipa joins other promising candidates for 213 Bi 3+ chelation that have arisen in recent years. , Ongoing work is directed toward the synthesis of a bifunctional analogue of py-macrodipa to apply this chelator in TAT, as well as the development of “macrodipa-type” chelators with enhanced Ac 3+ complex stabilities.…”
mentioning
confidence: 96%
“…NMR spectroscopy indicated that the complex interconverts between the two enantiomeric pairs in solution. [89] The [Bi(DOTP)] 5complex was shown to have a formation constant of 10 38.7 and significant kinetic inertness (t 1/2 , pH 3 ¼ 47000 h). [89] H 8 DOTP displayed an impressive ability to achieve 213 Bi radiolabelling efficiencies of ,90 % at RT and ligand concentrations of 10 À4 M that was comparable with CHX-A-DTPA under the same conditions.…”
Section: Bismuthmentioning
confidence: 98%
“…[89] The [Bi(DOTP)] 5complex was shown to have a formation constant of 10 38.7 and significant kinetic inertness (t 1/2 , pH 3 ¼ 47000 h). [89] H 8 DOTP displayed an impressive ability to achieve 213 Bi radiolabelling efficiencies of ,90 % at RT and ligand concentrations of 10 À4 M that was comparable with CHX-A-DTPA under the same conditions. [87] Comparison stability studies showed that [ 213 Bi][Bi(H 4 DOTP)]was more stable than [ 213 Bi][Bi(DOTA)]and [ 213 Bi][Bi(CHX-A-DTPA)] 2in both human plasma and to an excess of DTPA 5over 3 h. The faster formation kinetics could be due to the affinity of the Bi 3þ ion for phosphonate oxygen atoms and/or the orientation of the phosphonate groups (two above and two away from the ring N atoms), which is in contrast to H 4 DOTA, where all four carboxylates are positioned above the plane of the ring N atoms.…”
Section: Bismuthmentioning
confidence: 98%
See 1 more Smart Citation
“…These conditions are hardly compatible with the preparation of labile bioconjugates and detrimental in terms of residual radio-activity, taking a time comparable to one half-life of 213 Bi. [9,10] The variation of the pendant arms of the macrocyclic CAs was demonstrated to be a possible strategy to speed up the formation kinetics of Bi III -complexes. [11] The phosphonate analogue DOTP was recently shown to combine a higher thermodynamic stability with a faster complexation kinetics with respect to the carboxylic counterpart.…”
Section: Introductionmentioning
confidence: 99%